COMBINED ACTION ANTIHYPERTENSIVE AGENT URAPIDIL: EFFECTIVENESS AND SAFETY IN CLINICAL PRACTICE - N. I. Gaponova; V. R. Abdrakhmanov; V. A. Kadyshev; A. Yu. Sokolov (Кардиоваскулярная терапия и профилактика)
The paper reviews the clinical practice potential of a combined action antihypertensive medication urapidil for the treatment of patients with acute elevation of blood pressure (BP) and confirms urapidil effectiveness and good tolerability. Urapidil action mechanisms, pharmacodynamics, and pharmacokinetics are discussed, together with the results of the key clinical trials which have demonstrated antihypertensive effectiveness and safety of this agent. Additional beneficial effects of urapidil, such as reduction of the increased pulmonary artery BP and improvement of bronchial conductivity, are also described.